Differentiation of deer tendons from cattle tendons by a loop-mediated isothermal amplification (LAMP) test and bone remodeling bioassays. Issue 1 (December 2015) - Jiang, Li-Li; Liu, Cheuk-Lun; Wong, Yuk-Lau; Nip, Chun-Fong; Shaw, Pang-Chui
Abstract Background Deer tendons are believed more effective than cattle tendons in tonifyingkidney yang (shen yang ) and enhancing bone and tendons. This study aims to differentiate the two types of tendons by a loop-mediated isothermal amplification (LAMP) test and bone remodeling bioassays. Methods Internal control primers to detect both types of tendons and specific primers for deer tendons were designed according to a sequence analysis. The LAMP test was set up and the results were analyzed by conventional gel electrophoresis, real-time fluorescence observation, and colorimetric detection. Crude tendon extracts were prepared by water extraction to compare their effects on bone. The anti-osteoclastic effects were investigated on mouse pre-osteoclast Raw264.7 cells by cell viability determination and tartrate-resistant acid phosphatase staining. The osteogenic effects were examined using rat osteoblast-like UMR106 cells by evaluation of cell proliferation, alkaline phosphatase activity, and calcium deposition. The relative gene expressions of bone remodeling-related markers, including nuclear factor of activated T-cells cytoplasmic 1, tartrate-resistant acid phosphatase, cathepsin K, and osteoprotegerin/receptor activator of NF-κB ligand, were determined by real-time PCR. Results In the LAMP test, both deer and cattle tendons were detected in the control reactions, while only deer tendons were amplified by the specific LAMP test. In the bioassays, both tendons inhibited the viability and differentiation of pre-osteoclast Raw264.7 cells, and promoted the proliferation and mineralization of osteoblast-like UMR106 cells. The mRNA expressions of bone remodeling-related markers were consistent with the results of the bioassays. Conclusion This study demonstrated that the isothermal LAMP test can distinguish between deer tendons and cattle tendons. Both types of tendons exhibited similar beneficial effects on bone remodeling according to the bioassay findings.